In vitro screening of selected essential oils from medicinal plants acclimated to Benin for their effects on methane production from rumen microbial fermentation - KOUAZOUNDE, BAMIKOLÉ JACQUES; JIN, Long; McALLISTER, Tim A.; GBENOU, Djimon Joachim (My University, 2016)
Enteric methane production lowers the efficiency of feed utilization in ruminants and contributes to greenhouse gas emissions which are responsible for global climate change. This study examined the effects of nine essential oils (EO) from C. aurantifolia, C. citratus, E. citriodora, L. nobilis, L. multiflora, M. piperita, O. basilicum, O. gratissimum and Z. officinalis on enteric CH4 production in in vitro batch cultures screening experiments using A. gayanus grass. Two in vitro batch culture incubation runs were conducted independently on separate days at two different ranges of dosages: 0 (control), 150, 300, 600 and 1200 mg L-1 inoculum and 0 (control), 25, 50, 100 and 150 mg L-1 inoculum. The effects of EO on in vitro gas production, CH4 production and apparent dry matter disappearance (DMD) were assessed relative to the control containing no additive. Ocimum basilicum, E. citriodora, O. gratissimum and C. aurantifolia, significantly inhibited (Z’ ˃ 0 and relative decrease ≥ 15%) enteric CH4 production (g dry matter (DM) incubated) relative to control at dosages of 300-1200 mg L-1 and L. nobilis, C. citratus and M. piperita significantly decreased it at 600 and 1200 mg L-1. A substantial decrease (Z’ ˃ 0 and relative decrease ≥ 15%) in CH4 production per g DM incubated was apparent for Z. officinalis and L. multiflora at dosage of 1200 mg L-1. Most EO had globally negligible effects on CH4 production (Z’ ≤ 0 and relative decrease < 15%) at dosages of 25 to 150 mg L-1. Substantial decrease in apparent DMD together with gas production (g DM) incubated was observed relatively to the control with Z. officinalis and L. multiflora at 1200 mg L-1 and with the remaining EO at 600 and 1200 mg L-1. Overall, this screening investigation demonstrated that addition of assayed EO (except Z. officinalis and L. multiflora) at dosages close to 300 mg L-1 seem to potentially decrease enteric CH4 production with limited negative effects on DM digestibility of forage grass in vitro.
Keywords: Essential oil; in vitro; rumen; digestibility; methane production